"Ma chambre" ou: comment linéariser l'espace: Etude ontogénétique de textes descriptifs écrits - Schneuwly, Bernard; Rosat, Marie-Claude (My University, 1995)
This ontogendic study analyzes how children of different ages transform a three-dimensional space into a linear written text. At this end, 20 students aged 8,10,12 and 14 describe their bedroom in a short written text. Three dimensions of the texts are analyzed: the ratio of spatial to other informations given; the categories of expressions of space used; the overall structure of the texi. The results show that the youngest students do not organjze the text following spatial dimensions, but enumerate objects situated in the room in using very simple, repetitive syntactic structures. The 10 years olds group objects in relation to each other, but without situating them in an objective space. The 12 years old organise the text foIlowing a gaze tour strategy which in itseIf is net situated in function of a dear defined framework. The 14 years old finally define an objective framework wich allows to situate the objects in an independant space; this allows at the same time to give the text a dominant topic and a well marked textual structure.